The Role of Multicultural Education Toward Students' Creative Thinking Skills (Case Study on Kaki Dian Emas Foundation, Indonesia) - Ritwan Imanuel Tarigan (Journal of Management Practices, Humanities and Social Sciences, 2019)
The aim of this study is to investigate the relationship between multicultural education and students' creative thinking skills. The link between education and multiculturalism is a solution to diverse cultural realities as a process of developing all potential that respects plurality as well as heterogeneity as a consequence of cultural diversity. Previously scholars have investigated and found that multicultural education can predict betterperformance in steps of creative thinking skills. The Kaki Dian Emas Foundation with its From Lawang to Sentul (FLaTS) program places multicultural education as a training curriculum where through appreciation of differences can enhance creative thinking skills during the training process. In another study, through socio-cultural theories proves that multicultural interactions can enhance creative thinking skills and the role of cognitive flexibility rather than multicultural exposures. The research objective to be achieved is to find out and analyze the role of multicultural education on students' creative thinking skills. In the implementation, this study took primary data using questionnaires. Secondary data is obtained from the Foundation Secretariat. The type of research used is using quantitative research with explanatory methods. The number of respondents was 46 students of FLaTS Batch XXXII. Primary data obtained by using questionnaires. The analysis technique used is using the Moderated Regression Analysis (MRA) or interaction test. Based on the results of the analysis and discussion, the conclusions of the study are: Multicultural interactions in which there are values of appreciation and are open to each other to differences will provide a significant relationship to the dimensions in creative thinking skills. The form of in-depth multicultural education in FLaTS accommodates repeated interactions in a continuous time so that it expands the creative thinking process of students.